1997
DOI: 10.1007/s004210050240
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response at the onset of voluntary exercise and passive movement in endurance runners

Abstract: The present study was performed to examine whether or not the ventilatory response at the onset of voluntary exercise and passive movement in endurance runners is the same as in untrained subjects. Twelve long-distance runners belonging to the varsity athletic club and 13 untrained subjects of our university participated as subjects in this study. Maximum oxygen uptake was significantly higher in the endurance runner group [mean (SD) 70.8 (4.7) ml.kg-1.min-1] than in the untrained group [49.8 (6.3) ml.kg-1.min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…Rhythmic limb movements that have been confirmed to be largely passive in humans (Bell et al 2003) are associated with a rapid increase in the minute ventilation (Dejours et al 1959;Ishida et al 1994;Sato et al 2000) and frequency of breathing (Bell et al 2003;Ishida et al 1994;Miyamura et al 1997). Interestingly, subjects with clinically complete spinal cord injuries did not show the increase in minute ventilation with passive movements (Jaeger-Denavit et al 1973;Morikawa et al 1989) and those with incomplete lesions showed ventilatory changes that were intermediate between healthy controls and those with clinically complete spinal cord injuries (Jaeger-Denavit et al 1973).…”
Section: Rate Of Breathing Is a Function Of The Rate Of Steppingmentioning
confidence: 99%
“…Rhythmic limb movements that have been confirmed to be largely passive in humans (Bell et al 2003) are associated with a rapid increase in the minute ventilation (Dejours et al 1959;Ishida et al 1994;Sato et al 2000) and frequency of breathing (Bell et al 2003;Ishida et al 1994;Miyamura et al 1997). Interestingly, subjects with clinically complete spinal cord injuries did not show the increase in minute ventilation with passive movements (Jaeger-Denavit et al 1973;Morikawa et al 1989) and those with incomplete lesions showed ventilatory changes that were intermediate between healthy controls and those with clinically complete spinal cord injuries (Jaeger-Denavit et al 1973).…”
Section: Rate Of Breathing Is a Function Of The Rate Of Steppingmentioning
confidence: 99%
“…These data were stored on a hard disk unit, and analyzed afterward on a personal computer (NEC, PC-9821Xa, Japan). Breath-by-breath and beat-by-beat data were aligned with the onset of each turn, linearly interpolated between each breath or beat to yield a data point at each 1 s interval, and the ensemble average was done across all three repetitions [16,17]. The peak attained times of V .…”
Section: Short Communicationmentioning
confidence: 99%
“…However, the underlying neural cardiovascular mechanisms of training-related alterations in R-R interval responses at the onset of exercise are not understood. Thus, previous studies have addressed this issue considering the possibility of neural changes in the relative role of the muscle mechanoreflex and its inhibitory effect on cardiac vagal activity (8)(9)(10)(11)(12). Additionally, passive movement is widely employed to estimate the effect of the muscle mechanoreflex in humans (10,(13)(14)(15), because the effect of central command can be removed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, passive movement is widely employed to estimate the effect of the muscle mechanoreflex in humans (10,(13)(14)(15), because the effect of central command can be removed. Human studies examining the influence of exercise training on the heart rate response at the onset of passive movement have used a cross-sectional design (11,12), making comparisons between trained and untrained subjects. These investigators noted that the heart rate increase throughout 20 s of passive movement is attenuated in endurance runners (11) and sprinters (12) compared to untrained subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation